Chemotherapy regimen and incidence of malnutrition after chemotherapy in non-small cell lung cancer - Buntitabhon Sirichancheun (2019)
© 2019 Sirichancheun et al. Lung cancer is the leading cause of death worldwide and in Thailand. The treatment of non-small cell lung (NSCLC) with chemotherapy might affected on nutritional status which could correlate with the treatment response and quality of life. Thus, the objectives of this research were to study the nutritional status of patients after chemotherapy and the incidence of malnutrition. This retrospective longitudinal descriptive study was gathering the information from medical records January, 2013 to December, 2014. A 114 patients were met the inclusion criteria which were completed 4 or 6 cycles of treatment. Body mass index (BMI) and percentage of weight loss were used to assess the nutritional status. Malnutrition was classified when BMI under 18.5 kg/m2 and weight change more than 5%. The average age, baseline weight and BMI were 60.4±10.1 year, 55.0±9.0 kg and 22.0±2.5 kg/m2, respectively. The incidence of malnutrition was 6.1%. Mean BMI decreased from 22.0 kg/m2 to 21.5 kg/m2 after chemotherapy. Patients treated with carboplatin plus paclitaxel showed the highest change of BMI (-0.6 kg/m2) and docetaxel regimen showed the highest incidence of malnutrition (18.8%). According to the base agents; taxane-based regimen showed the most effect on nutritional status and 85% of those patients were malnutrition. In conclusion, docetaxel and carboplatin plus paclitaxel highly affected on nutritional status. In patients treated with those regimens, they should be closely monitored and gave an adequate nutritional advice for the better treatment response, decrease the side effect from chemotherapy and improve patients' quality of life.